1980
DOI: 10.1037/0022-3514.38.5.751
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal perception and mode of resolution in marital conflict.

Abstract: The present study examined the relationship between changes in couples' perceptions of each other during a conflictual interaction and their mode of conflict resolution. Thirty-three volunteer married couples were videotaped while recreating a conflictual interaction that had occurred previously. During a subsequent replaying of the videotape, husbands' and wives' verbal descriptions of perceptions of self and spouse were elicited at three different stages of the conflict, using a method for eliciting percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

1982
1982
2014
2014

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 18 publications
2
41
0
1
Order By: Relevance
“…This is reflected most clearly in studies reporting a positive association between marital adjustment and understanding of the attitudes, role expectations, and self-perceptions of one's spouse (Dymond, 1954;Corsini, 1956;Stuckert, 1963;Laing et al, 1966;Taylor, 1967;Christensen & Wallace, 1976;Murstein& Beck, 1972;Losee, 1976;Newmark, Wood, & Ziff, 1977;Ferguson & Allen, 1978). In several of these studies the relationship between understanding and marital adjustment has been found to hold only when the wife is the respondent and the husband's perception is being predicted (Stuckert, 1963;Murstein& Beck, 1972;Corsini, 1956;Kotlar, 1965).…”
Section: Interpersonal Perception and Relationship Adjustmentmentioning
confidence: 89%
“…This is reflected most clearly in studies reporting a positive association between marital adjustment and understanding of the attitudes, role expectations, and self-perceptions of one's spouse (Dymond, 1954;Corsini, 1956;Stuckert, 1963;Laing et al, 1966;Taylor, 1967;Christensen & Wallace, 1976;Murstein& Beck, 1972;Losee, 1976;Newmark, Wood, & Ziff, 1977;Ferguson & Allen, 1978). In several of these studies the relationship between understanding and marital adjustment has been found to hold only when the wife is the respondent and the husband's perception is being predicted (Stuckert, 1963;Murstein& Beck, 1972;Corsini, 1956;Kotlar, 1965).…”
Section: Interpersonal Perception and Relationship Adjustmentmentioning
confidence: 89%
“…The general research plan calls for methodological and substantive analyses based on each method independently, and then for the study of relationships among methods as the comparability of procedures may allow. Some findings based on interaction records and one of the analogues have already been reported (Knudson, Sommers, & Golding, 1980;Peterson, 1979a). Downloaded by [Deakin University Library] The present analysis is the first in which relationships among procedures have been examined.…”
Section: Methodsmentioning
confidence: 81%
“…The interactions between the victim and the perpetrator can also have consequences for victim responses. For instance, past research has shown that couples who try to resolve conflict in an open and direct manner tend to develop a more accurate understanding of their partner's thoughts and feelings compared to those who avoid conflict (Knudson, Sommers, & Golding, 1980). In addition, past research has shown that discussing an issue openly can clarify misunderstandings about why an event occurred (e.g., Gottman, 1994;Hilton 1990).…”
Section: Theory and Research On Forgivenessmentioning
confidence: 99%